Analysis of seasonal variability of wave height in Makassar Strait. Issue 1 (January 2021) - Labania, H M D; Mudin, Y; Rahman, A; Sabhan,; Pranowo, W S
Abstract: This study was conducted to examine spatially the seasonal variability of sea wave characteristics in the Makassar Strait waters by utilizing the third generation wave model, MIKE 21 Spectral Wave Model. The study was conducted by observing seasonal variability of sea wave height in Makassar Strait waters for 10 years. The data used are wind data predicted by ECMWF every 6 hours during the period 2006 - 2015 as the main input of wave energy generation. The domain model is adjusted to the wind configuration in a uniform grid size of 5' x 5' which is considered to be sufficient to represent the bathymetry of the Makassar Strait waters with location limits of 1, 00 0 LU - 3, 98 0 LS and 116, 15 0 BT - 120, 30 0 BT and 15 stations. Based on the results of the study, showed that high waves occur in the west season which tends to follow the monsoonal pattern according to the local climate type. The maximum significant wave height tends to occur in the western, central and southern waters of the Makassar Strait with an average observed in the middle of the year in the June, July and August periods (east monsoon). For the study of coastal waters, maximum wave height fluctuations tend to be uniform.